Thalassobacillus pellis sp nov., a moderately halophilic, Gram-positive bacterium isolated from salted hides - BİRBİR, MERAL; ÇAĞLAYAN, PINAR (MICROBIOLOGY SOC, 2011)
A Gram-positive, moderately halophilic and endospore-forming bacterium, designated strain 18OM(T), was isolated from salted animal hides. The cells were rods and produced ellipsoidal endospores at a terminal position. Strain 18OM(T) was motile, strictly aerobic and grew at 0.5-25% (w/v) NaCl [optimal growth at 10% (w/v) NaCl], at between pH 5.0 and 9.0 (optimal growth at pH 7.5) and at temperatures between 15 and 45 degrees C (optimal growth at 37 degrees C). Phylogenetic analysis based on 16S rRNA gene sequence comparisons showed that strain 18OM(T) was closely related to species of the genus Thalassobacillus within the phylum Firmicutes. The closest phylogenetic similarity was with Thalassobacillus devorans G-19.1(T) (98.4%), Thalassobacillus cyri HS286(T) (97.9%) and Thalassobacillus hwangdonensis AD-1(T) (97.4 %). The major cellular fatty acids were anteiso-C-15:0 (57.9 %), anteiso-C-17:0 (14.0 %), isoC15:0 (10.8%) and iso-C-16:0 (8.1%). The respiratory isoprenoid quinones were MK-7 (98.5 %) and MK-6 (1.5%). The DNA G +C content was 42.9 mol%. These features confirmed the placement of strain 18OM(T) within the genus Thalassobacillus. The DNA-DNA hybridization values between strain 18OM(T) and T. devorans G-19.1(T), T. cyri H5286(T) and I hwangdonensis AD-1(T) were 49%, 9% and 15%, respectively, showing unequivocally that strain 18OM(T) constituted a novel genospecies. On the basis of phylogenetic analysis and phenotypic, genotypic and chemotaxonomic characteristics, strain 18OM(T) is considered to represent a novel species of the genus Thalassobacillus, for which the name Thalassobacillus pellis sp. nov. is proposed. The type strain is 18OM(T) (=CECT 7566(T)=DSM 22784(T)=JCM 16412(T)).
Keywords: GEN. NOV.; DEOXYRIBONUCLEIC-ACID; SPECIES DEFINITION